Vancomycin-Loaded Nanoparticles Enhance Sporicidal and Antibacterial Efficacy for Clostridium difficile Infection - Chen, Yi-Hsuan; Li, Tsung-Ju; Tsai, Bo-Yang; Chen, Liang-Kuei; Lai, Yi-Hsin; Li, Meng-Jia; Tsai, Cheng-Yang; Tsai, Pei-Jane; Shieh, Dar-Bin (Frontiers in Microbiology, 2019)
Current antibiotic treatments fail to eliminate the Clostridium difficile (C. difficile) spores and induce dysbiosis and intestinal inflammation via off-target effect, which causes refractory C. difficile infection raise an unmet need for a spore-specific antimicrobial treatment. We developed a sporicidal and antimicrobial vancomycin-loaded spore-targeting iron oxide nanoparticle (van-IONP) that selectively binds to C. difficile spores. Cryo-electron microscopy showed that vancomycin-loaded nanoparticles can target and completely cover spore surfaces. They not only successfully delayed the germination of the spores but also inhibited ~50% of vegetative cell outgrowth after 48 hours of incubation. The van-IONPs also inhibited the interaction of spores with HT-29 intestinal mucosal cells in vitro. In a murine model of C. difficile infection, the van-IONP significantly protected the mice from infected by C. difficile infection, reducing intestinal inflammation, and facilitated superior mucosal viability compared with equal doses of free vancomycin. This dual-function targeted delivery therapy showed advantages over traditional therapeutics in treating C. difficile infection.